Marine Pollution in Kuwait and Its Impacts on Fish-Stock Decline in Kuwaiti Waters: Reviewing the Kuwaiti Government's Policies and Practices - Alqattan, Mohammad E. A.; Gray, Tim S. (Frontiers in Sustainability, 2021)
Kuwait’s ‘Blue Economy’ project aims to help replace the country’s oil and gas income by the sustainable development of its marine resources. The fishing industry has a prime place in the ‘Blue Economy’ project, but nine of the main fish species in Kuwait have recently declined Rubian (Shrimp), Zobaidi (Silver Pomfret), Suboor (Hilsa Shad), Naqroor (Javelin Grunter), Hamoor (Orange-Spotted Grouper), Hamra (Malabar Blood Snapper), Halwayuh (Black Pomfret), Frush (Trout Sweetlips) and Kasur (Lizard Fish). This paper investigates the nature of pollution in Kuwaiti waters, examining its extent and causes, questioning whether or not it is a primary reason for fish decline, and discussing what measures could be taken to reduce or remove it. The data for this study were gathered from peer-reviewed articles, official Kuwaiti statistics and reports, and semi- structured interviews conducted in Kuwait with stakeholders in the fisheries including staff in the Kuwaiti Scientific Institute, the Fishery Protection Authority, the Environmental Protection Authority and governmental departments; fishers; and fishery business owners. The main finding of this study is that because of the weak government policies and practices to counter pollution, pollution does exist in Kuwaiti waters, but there is no solid evidence that it has a direct link to the decline in fish stocks. Overfishing, especially by illegal, unreported and unregulated (IUU) vessels, seems to be a more substantial cause of the decline in fish stocks.